A Hybrid Ameloblastoma in Posterıor Mandible: A Case Report - Alper Sindel; Büşra Altunay; Gülay Özbilim; Öznur Özalp; Büşra Karasu (Selçuk University, 2024)
Objective: Hybrid ameloblastoma refers to the tumors that contain two or more different histologic types of ameloblastoma. Till date, only 49 cases of hybrid ameloblastoma with different combinations have been reported. Here we present a case of hybrid ameloblastoma containing follicular, plexiform, and acanthomatous types. Case Report: A 24-year-old male patient referred to our clinic with a slow-growing asymptomatic swelling on the right side of the mandible. Radiographic assessment revealed a well-defined radiolucent lesion associated with an impacted third molar. Following incisional biopsy, which was compatible with ameloblastoma, total excision of the lesion along with Carnoy fixation was performed. Final histopathologic assessment revealed a hybrid ameloblastic lesion which contained follicular, plexiform, and acanthomatous types. Conclusion: Hybrid ameloblastoma has variable clinical, radiological, and histopathological presentation. As a rare entity, the biological behavior of the lesion still needs to be analyzed extensively with further clinical research. Keywords: Carnoy, Enucleation, Hybrid ameloblastoma.